Methane hydrate re-formation and blockage mechanism in a pore-level water-gas flow process. (15th January 2023) - Sun, Huiru; Chen, Bingbing; Li, Kehan; Song, Yongchen; Yang, Mingjun; Jiang, Lanlan; Yan, Jinyue
Abstract: Hydrate re-formation increases blockage risk and further reduces gas production efficiency. Considering the huge water production and gas migration, it is essential to determine the key parameters that control hydrate re-formation and blockage in the two-phase flow process. However, little research reveals the mechanism of hydrate re-formation in the water-dominated two-phase flow system. In this study, two-phase flow in hydrate sediment is simulated by controlling the water-gas flow rate, and the effect of effective sectional velocity on hydrate re-formation characteristics is analyzed. The experimental results showed that temperature and pressure followed a three-stage change trend in the water-dominated two-phase flow process: including hydrate re-formation induction stage I, mass hydrate re-formation and agglomeration stage II, and pore gas consumption stage III. Moreover, a lower effective sectional velocity of water (WESV) would reduce the gas concentration gradient between water and hydrate to enhance the hydrate re-formation process. Meanwhile, the gas phase impeded the mass transfer on the water-hydrate interface and acted as the nucleation site to promote hydrate re-formation. Furthermore, it was noticed that the relationship between the onset time of flow blockage and WESV was linearly positive, however, the amount of hydrate re-formation reduced with increasing WESV. Graphical abstract: Image 1 Highlights: MH re-formation mechanism in water-dominated two-phase flow process is revealed. Change in pressure and temperature shows a three-stage trend due to MH re-formation. Onset time of blockage is positively related to the effective sectional velocity of water. MH re-formation amount is negatively related to the effective sectional velocity of water.